Mental health advocacy on Twitter: Positioning in Depression Awareness Week tweets. (October 2018) - Koteyko, Nelya; Atanasova, Dimitrinka
Highlights: The study examines tweets about depression tagged with #WhatYouDontSee. Results reveal different uses of metadata and images for interactional positioning. Audiences are positioned as jury, confidantes, and fellow sufferers. The positions allow users to bear witness, validate experiences, and invite judgement. Analysis highlights the interactional function of digital illness narratives.